The quality in psychiatric care-Addiction outpatient instrument: Psychometric properties and patient views of the quality of care - Agneta Schröder; Kurt Skårberg; Lars‐Olov Lundqvist (Wiley, 2021)
Abstract Aim The aim of the study was to evaluate the psychometric properties and factor structure of the Quality in Psychiatric Care-Addiction Outpatient (QPC‐AOP) instrument and to describe the experiences with the quality of care among addiction outpatients. Design The study has a cross‐sectional design. Methods A sample of 244 patients with addiction and psychiatric disorders completed the QPC‐AOP. Results Confirmatory factor analysis showed adequate to excellent goodness‐of‐fit indices supporting the 9‐factor structure of the QPC‐AOP. The results thus demonstrate that the concept of quality of care to a large extent is equivalent among outpatients from general psychiatry and from outpatient addiction services. Internal consistency for the full QPC‐AOP was adequate, but poor for some of the separate factors. The patients' ratings of quality of care were generally high; the highest rating was for Encounter and the lowest for Discharge.